2023
DOI: 10.1002/bmc.5624
|View full text |Cite
|
Sign up to set email alerts
|

Separation and quantification of diazinon in water samples using liquid‐phase microextraction‐based effervescent tablet‐assisted switchable solvent method coupled to gas chromatography‐flame ionization detection

Abstract: This study used a liquid‐phase microextraction‐based effervescent tablet‐assisted switchable solvent method coupled to gas chromatography‐flame ionization detection as an eco‐efficient, convenient‐to‐use, cost‐effective, sensitive, rapid, and efficient method for extracting, preconcentrating, and quantifying trace amounts of diazinon in river water samples. As a switchable solvent, triethylamine (TEA) was used. In situ generation of CO2 using effervescent tablet containing Na2CO3 and citric acid changed the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, its use has led to contamination of surface waters in many parts of the world, including the United States [ 1 , 2 , 3 ]. Studies have found traces of diazinon in streams, rivers, and lakes due to runoff from agricultural and residential areas [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, its use has led to contamination of surface waters in many parts of the world, including the United States [ 1 , 2 , 3 ]. Studies have found traces of diazinon in streams, rivers, and lakes due to runoff from agricultural and residential areas [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The highest levels of diazinon were observed immediately after insecticide spraying, but no traces were detected after a few months. Despite this, diazinon is a persistent pesticide in aquatic environments due to continuous inputs over time [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation